Human rights after Deleuze : towards an an-archic jurisprudence - Marneros, Christos (London [England] : Hart Publishing, 2022)
"The book draws upon Deleuze's broader thought, but also radical legal and political theory and continental philosophy to examine the possibility of creating new ways of existing and doing politics beyond human rights. The multiple socio-political crises and the dominance of neoliberal and capitalist policies have led legal and political theorists to question the emancipatory promise of human rights. These scholars tried to reassess and reconceptualise human rights in theory and practice. Having as its starting point the ferocious, yet brief, critique on human rights of one of the most prominent French philosophers of the 20th century, Gilles Deleuze, the book argues that Deleuze's critique is not only compatible with his broader thought but it has the potential to give a new impetus to the current critiques of human rights, within the 'disciplinary borders' of legal and political theory. The book investigates and expands on two of Deleuze's most important notions, namely those of 'immanence' and 'becoming' and their relation to the philosopher's critique of human rights. In doing so, it argues that these two notions are capable of questioning the dominant and dogmatic position that human rights enjoy. Ultimately, by critically examining and expanding on Deleuze's use of the term 'jurisprudence', the book argues for an account of doing politics beyond human rights - what it calls an an-archic jurisprudence."--
1. Introduction -- 2. Deleuze and Human Rights -- 3. The Question of Immanence -- 4. Immanent Ethics and Transcendent Morality: Deleuze's An- archic Ethos -- 5. Questioning the Subject of Rights, or How is a Deleuzuian Becoming? -- 6. Deleuze's Jurisprudence: Is There Phronesis Beyond Human Right -- 7. Apodosis: Towards an An-archic Jurisprudence -- Bibliography -- Index
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Deleuze, Gilles, -- 1925-1995 -- Criticism and interpretation; Human rights -- Philosophy; Electronic books